The Effectiveness of Problem Based Learning Model in Improving Students' Conceptual Understanding in Islamic Education Learning - Ariani, Safrina (Jurnal Pengembangan Profesi Guru dan Dosen, 2024)
This study aims to improve students' conceptual understanding ability by applying the problem based learning model. This study is a classroom action research. The subjects of this study were elementary school students. Data were collected using observation and test techniques. The collected data were analyzed using descriptive statistical techniques. The results of the study indicate that the use of the problem based learning model can improve the learning outcomes of Islamic Religious Education on the material of Asmaul Husna examples in grade IV students of SDN 15 Meulaboh, Johan Pahlawan District, West Aceh Regency. Furthermore, there is a comparison of the increase in the average value of the learning outcome test in each cycle, namely in the initial condition the average value was only 80.66% with learning completeness only reaching 74.3%. After being given action in cycle I, the average value of students increased to 85.00% with learning completeness reaching 92.3%. In cycle II the average value increased again. Based on these results, the problem based learning model can be used as an alternative model in an effort to overcome the problem of low students' conceptual understanding ability.